2001
DOI: 10.1007/s004050100357
|View full text |Cite
|
Sign up to set email alerts
|

Post-intubation vocal cord paralysis: the viral hypothesis. A case report

Abstract: After digestive surgery, a 20-year-old man presented dysphonia and fever. Indirect laryngoscopy revealed a left vocal cord paralysis with no structural lesion. IgM and IgG were positive for cytomegalovirus and negative for human immunodeficiency virus, herpes simplex virus, varicella zoster virus and Epstein-Barr virus. The patient recovered spontaneously with a normal voice, and the mobility of vocal cord recovered within 3 months. The aetiology of post-intubation vocal cord paralysis (VCP) remains controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Vocal cord paralysis without a history of intubation has been reported in association with herpes simplex virus, varicella zoster virus, EBV and cytomegalovirus. 13 Mechanical and neurogenic mechanisms have been proposed, however, causality or an exact pathogenic mechanism have not been established. Extension of adjacent inflammation can cause unilateral or bilateral reduction in mobility of the small muscles and joints of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal cord paralysis without a history of intubation has been reported in association with herpes simplex virus, varicella zoster virus, EBV and cytomegalovirus. 13 Mechanical and neurogenic mechanisms have been proposed, however, causality or an exact pathogenic mechanism have not been established. Extension of adjacent inflammation can cause unilateral or bilateral reduction in mobility of the small muscles and joints of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism could be the compression of the recurrent laryngeal nerve by the lateral arytenoids, thyroid cartilage and an inflated cuff from an endotracheal tube [1] . Marie et al [14] advocated that the recurrent laryngeal nerve, after intubation, could suffer from viral infections triggered after local trauma, such as herpes zoster. In addition, trauma causing VCP may be due to traffic accidents and penetration of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of cases (29.8–65.7%) are reported as idiopathic in etiology [ 8 ]. Many speculate that viral etiologies could account for a significant portion of the cases currently considered idiopathic [ 9 ]. Retrospective studies have supported this and found that a high number of upper respiratory infections correlated with idiopathic cases of VCP [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%